Um estudo sobre currículo na educação infantil na produção científica da ANPEd nos últimos dez anos - Andreza Maria de Lima; Maria Jaqueline Paes de Carvalho; Luciana Oliveira Freitas Monteiro (EccoS – Revista Científica)
This study aimed to map and analyze the scientific production about curriculum in kindergarten during the last ten years, in the annals of ANPEd. As base materials, it were used the works of the GT07 (Education of children 0-6 years old) and GT12 (Curriculum), available on the website of the Association. After mapping it, the analyzis was conducted guided by a script to identify the research cycle. Five studieswere located. This result indicated the need for research on curriculum in kindergarten. The analysis of these studies showed a lack of systematic theoretical discussion about curriculum, although most os them show the designing curriculum adopted. Regarding methodology, two studies did not indicate the procedures for data collection/production and analysis used. The findings indicate the importance of these structures in written articles, for researchers. It is emphasized the need to investigate other GTs for a more consistent view of this production.